Al- Mughni Al- Kabir: A Dictionary of Contemporary English: English- Arabic with Illustrations and Coloured Plates: (3GdeZfj GdcHjQ(B: (3eYLe GddZI GdEfLdjRjI GdeYGUQI hGdMOjKI(B: (3EfcdjRj(B- (3YQHj ehVM HGdQShe hGddhMGJ GdedhfIs - Hasan Said Karmi (3MSf SYjO cQejs (Lebanon (3ecJHI dHfGfs, 1991)
(3GdZGjI ef gPG GdeYLe gh ChdkG EYWGA GdeYGfj GdUMjMI ddcdeGJ GdEfcdjRjI, hYOOgG bQjH ef SJjf CdakG, hKGfjkG JYdje GddZI GdEfcdjRjI Yf WQjb GSJYeGdgG aj Led eNJGQI(B. (3hGdeYQha Cf GdLedI YHGQI Yf cdeGJ ehVhYI aj JQJjH eYjf dCOGA eYfi eYjf(B. (3agj eJQGHWI, hHjfgG QhGHW JVe GdcdeGJ HYVgG Edi HYV, adG HO ef age GdcdeGJ, hage GdQhGHW Yf WQjb GdGSJYeGd, HGdTQM hGdThGgO, ceG gh GdMGd aj GSJYeGd (BSame, ever, enough, about... (3fXQI hGMOI Edi gPG GdeYLe JMJ cdeI ef gPg GdcdeGJ hZjQgG JQj cKQI GdCeKdI hGdLed GdEfcdjRjI Yf eNJda GdUhQ hGdeYGfj GdJj JSJYed ajgG gPg GdcdeI(B. (3gPG HGdEVGaI Edi GSJYeGdGJ GdCaYGd eY CMQa GdLQ hGdXQha hEdi GdGSJYeGdGJ GdYOjOI GdJj jSJYed ajgG GSe ef GdCSeGA, ceG gh eTQhM Yf GdaYd (BTake (3Ch (Bhold(3, Ch Yf GdGSe (Btinne (3Ch (Bhand (3eKdkG hYdi gPG aEf eYLe (B"(3GdeZfj GdcHjQ(B" (3HGSJYeGdg GdTQM GdhGaj hGdCeKdI hGdThGgO jYde GddZI GdEfcdjRjI aj GdcdGe hGdcJGHI, Hd Cfg HWQjb ZjQ eHGTQ jYde GddZI GdYQHjI(B. (3hdeG cGf ddZI GdEfcdjRjI WHjYI JNJda Yf WHjYI GddZI GdYQHjI, aEf GdeYLe eWGdH HEXgGQ cd WHjYI hEHQGRgG HaVd eG jhQOg ef eYGf jCJj HgG GdeDda aj ThGgOg HYO Cf jchf bO YQa GddZJjf eYQaI eHGTQI heGQSgeG RefkG WhjdkG(B. (3hGdeYLe (B"(3GdeZfj GdcHjQ(B" (3gh GdKGfj aj SdSdI ef eYGLe KdGKI(B: 1-(3GdeZfj, (B2-(3GdeZfj GdcHjQ, (B3-(3GdeZfj GdCcHQ(B. (3hGdeZfj GdcHjQ aj gPg GdSdSdI jeKd UdI GdhUd Hjf GdeZfj hGdeZfj GdCcHQ, hjMSf Hef jgJe HGdCOH ChdkG Ke HGdYdhe KGfjkG Cf jSJYed (B"(3GdeZfj GdcHjQ(B"(3, hHGdegJe HGdYdhe ChdkG hHGdBOGH KGfjkG Cf jSJYed (B"(3GdeZfj GdCcHQ(B". (3aj (B"(3GdeZfj GdcHjQ(B" 1368 (3UaMI eRjfI HGdQShe, aj cd efgG (B3 (3CYeOI ef GdeUWdMGJ GdEfcdjRjI(B-(3GdYQHjI HGdEVGaI Edi CcKQ ef NeSI hSJjf Cda eONd EfcdjRj hCQHYhf Cda JYHjQkG GUWdGMj hdhMGJ EjVGMjI YdejI hafjI hCWdS GdHdGO GdYQHjI hGdbGQGJ hSJ hJSYhf dhMI EjVGMjI HGdCdhGf, ajgG fNHI ef GddhMGJ GdRNQajI GdYGdejI Edi LGfH bGehS eUhQ dLSe GdEfSGf(B. s
"(3GdeZfj GdCcHQ(B" (3gh hGMO aj SdSdI eYGLe (B"(3GdeZfj(B" (3GdeDdaI ef (B"(3GdeZfj GdCcHQ(B" ((3GfcdjRj(B-(3YQHj(B) (3h(B"(3GdeZfj GdcHjQ(B" ((3GfcdjRj(B-(3YQHj(B) "(3GdeZfj RGFO(B" ((3GfcdjRj(B-(3YQHj(B) (3GdeZfj GdhSjW (B((3GfcdjRj(B-(3YQHj(B) (3GdeZfj GdhLjR (B((3GfcdjRj(B- (3YQHj(B). (3hjYJHQ (B"(3GdeZfj GdCcHQ(B" (3ef Cge GdeYGLe GdeYJeOI YGdekG ceYLe GfcdjRj(B-(3YQHj ehKhb Hg(B. (3hehLg ddegJejf HGdYdhe ChdkG hHGdBOGH KGfjkG(B. (3hgh Edi gPG Zfj HGdQShe hGddhMGJ GdedhfI hGdedGMb hajg (B1728 (3UaMI eRjfI HGdQShe, aj cd efgG (B3 (3CYeOI ef GdeUWdMGJ GdGfcdjRjI(B-(3GdYQHjI hCcKQ ef (B100.000 (3eONd GfcdjRj h(B60.000 (3JYHjQ GUWdGMj HGdEVGaI Edi dhMGJ YdejI hKbGajI YGeI (B32 (3efgG HGdCdhGf h(B32 (3HGdCShO hGdCHjV(B.s
Keywords: Languages (3GddZGJs; General